Molecular Dynamics of the Transport of Ions in a Synthetic Channel - MORTON-BLAKE, DAVID (My University, 2014)
Abstract. Molecular dynamics investigations of ions in certain non-bulk media predict that they are capable of significantly greater mobilities than when in the liquid state. The entries of Li+, Na+, and K+ ions from electrolyte media into proposed synthetic channels consisting of fourteen 15-crownether- 5 (CE) rings bonded in stacked conformations are described and their subsequent dynamics in the channel discussed. The importance of channel flexibility is established by investigating two CE channels that are structurally similar but vary in the rigidity with which their rings are connected. The dynamics of cation channel migrants are simulated across a bilayer membrane between two bulk aqueous salt solutions and also when the channel floats freely in an aqueous medium. Various features of ion behaviour are investigated in the presence, and in the absence, of an electric field applied along the channel axis. The novel oscillatory behaviour of the ions in the channel is investigated, together with the possibility of their exits into the liquid medium. The frictional forces opposing the ion trajectories are calculated, found to be ~10 nN and attempts to formulate frictional laws for nanoscale systems are discussed.
PUBLISHED
Keywords: ion channels; molecular dynamics; synthetic channels; molecular friction; Creative Technologies; Nanoscience & Materials